Northern Region. Annual report 2007 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
This report summarizes the main activities and results obtained by the Directorate in 2007. The Directorate, in particular the DSP, plays an important role in representing specialists and managers from Headquarters in their dealings with institutions and organizations, many based in Washington, DC, that are already or they can potentially become strategic partners of IICA. Although this is the Northern Regional Report, many of the results reported here have been achieved thanks to technical support and coordination with IICA's technical staff.